Fermented foods and probiotic consumption frequency as protective indicators for peri-implant diseases - a cross-sectional study - Tugba Sahin (BMC, 2024)
Abstract Background Due to their modulatory effect on biofilm growth, bacterial gene expressions, and host-modulation effects, fermented foods and probiotic products could potentially have a protective role against peri-implant diseases. This cross-sectional study aimed to examine the association of consumption of fermented foods and products containing probiotics, with peri-implant health and diseases. Methods A total of 126 implants were included. The peri-implant health status (peri-implantitis, peri-implant mucositis, and peri-implant health) was assessed through Chicago's Classification of periodontal and peri-implant Diseases and Conditions. A questionnaire was used to evaluate the consumption patterns of fermented and probiotic foods and product. One-way ANOVA was employed to compare the 3 peri-implant conditions categories in terms of fermented food and probiotic consumption. Results There were significant differences in the daily and general consumption of yogurt, probiotic yogurt, kefir, ayran, vinegar, pomegranate syrup, whole meal bread, and homemade butter among peri-implantitis, peri-implant mucositis and peri-implant health (p < 0.05). The peri-implant health group consumed significantly more yogurt, kefir, ayran, vinegar, whole wheat bread, and homemade butter than peri-implant mucositis and peri-implantitis. Conclusion A higher consumption of fermented and probiotic foods may be associated with peri-implant health. Fermented and probiotic products may be useful for prevention of peri-implant diseases in patients with implants.